„Dzienniki mojego życia” Gustawa Zielińskiego – refleksje edytora - Król, Małgorzata (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article is an attempt to familiarise the readers with not only the source, Gustaw Zieliński’s Dzienniki mojego życia (Diaries of My Life), but also with the work on its first edition. Over a period of a few months (when these comments were noted down), the character of the text changed almost completely. One could even say that it transformed from a meticulously maintained personal text into a kind of notepad or sketchbook, which lost its diary-like character and became a sort of record of memories. The significance of this document, the range of themes discussed in it (among others, the literature, the social and cultural life of the first half of the 19th century) are all arguments in favour of taking up a laborious editorial work in order to publish this work. This article describes the stages of this work and discusses the ordering processes that make this source text interesting to a non-specialist reader.